Economic Impacts of the Forest Industry in Florida, 2003 - Alan W. Hodges; W. David Mulkey; Janaki R. Alavalapati; Douglas R. Carter; Clyde F. Kiker (EDIS, 2005)
Final Report to the Florida Forestry Association. Revised January 7, 2005. Press release 4/14/2005.